Variable Transmission Range Routing Protocol Based on Vehicle Density in VANET - Rong Cai; Guoan Zhang; Yuebo Wu (Dianxin kexue)
In order to solve the problem of unstable connectivity and high bit error rate,which are caused by rapid changes in the density of vehicles on the road,while the transmission radius remained unchanged,a variable transmission range routing protocols based on vehicle density in vehicular Ad-Hoc network was proposed.According to different vehicle density,node could adjust the farthest transmission distance and reduce the transmission latency of the message,which could ensure high connection probability of the network.Based on homogeneous poisson point process model,the change conditions of transmission range with different vehicle density were deduced,and its feasible was proved.Furthermore,mathematical calculate formula of average latency was obtained according to the theoretical analysis.At last,variable transmission range routing protocol based on vehicle density and fixed transmission range routing protocol were compared by simulation.The simulated results show that the proposed protocol can be applied in actual environments,and the message can be transmitted fast from source node to destination node under the condition of high connection probability.